2011
DOI: 10.1093/eurheartj/ehr360
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel pre-treatment is associated with reduced in-hospital mortality in primary percutaneous coronary intervention for acute ST-elevation myocardial infarction

Abstract: AIMS Pre-treatment with clopidogrel results in a reduction of ischaemic events in non-ST-elevation acute coronary syndromes. Data on upstream clopidogrel in the setting of primary percutaneous coronary intervention (PCI) are limited. The aim of this study was to investigate whether clopidogrel loading before arrival at the PCI centre may result in an improved outcome of primary PCI for ST-elevation myocardial infarction (STEMI). METHODS AND RESULTS In a multicentre registry of acute PCI, 5955 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 28 publications
1
32
1
3
Order By: Relevance
“…Notably, the administration of P2Y 12 inhibitors before catheterization in ST segment elevation myocardial infarction (STEMI) is recommended, and ideally, they should be administered at the time of the first medical contact. This recommendation is in keeping with American guidelines and is supported by a small randomized study [24], two observational studies [25, 26], and one meta-analysis [20] showing a reduction of death and MACE without increase of bleeding, in STEMI patients pretreated with clopidogrel.…”
Section: Antiplatelet Therapy and Revascularizationmentioning
confidence: 81%
“…Notably, the administration of P2Y 12 inhibitors before catheterization in ST segment elevation myocardial infarction (STEMI) is recommended, and ideally, they should be administered at the time of the first medical contact. This recommendation is in keeping with American guidelines and is supported by a small randomized study [24], two observational studies [25, 26], and one meta-analysis [20] showing a reduction of death and MACE without increase of bleeding, in STEMI patients pretreated with clopidogrel.…”
Section: Antiplatelet Therapy and Revascularizationmentioning
confidence: 81%
“…Data from registries and a metaanalysis showed that pretreatment with clopidogrel was associated with higher initial patency and improved outcome, including the combined endpoint of death and myocardial infarction at 1 year. [21][22][23][24] In contrast, in the CRUSADE initiative involving 3,785 patients with STEMI undergoing PPCI, the risk of adverse outcomes and bleeding events were similar in the pre-vs. peri-PCI clopidogrel cohorts, with reinfarction occurring more frequently in the pre-PCI group. 25 Of note, in the only so far randomized study, the early use of 600 mg clopidogrel had a similar effect to that of placebo on flow rates, possibly because of the short clopidogrel to angiography time.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, a report published by Stauffer et al, using data from the Acute Myocardial Infarction Swiss-Plus (AMIS Plus) registry, found, as in a similar Austrian study [30], that patients pretreated with combination of clopidogrel and percutaneous coronary intervention (PCI) had significantly lower morbidity and mortality, which may not be the case in settings with limited access to resources [31].…”
Section: Discussionmentioning
confidence: 96%